1997
DOI: 10.1111/j.1365-2249.1997.tb08332.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated soluble Fas/APO-1 (CD95) levels in silicosis patients without clinical symptoms of autoimmune diseases or malignant tumours

Abstract: SUMMARYSoluble Fas (sFas) is produced as translation products of alternative mRNA splicing, and antagonizes the membranous Fas molecule in Faspas ligand interactions. We investigated the serum sFas levels in 64 Japanese silicosis patients with no clinical symptoms of autoimmune diseases or malignant tumours, using ELISA for sFas. The serum sFas levels in the silicosis patients were significantly higher than those in healthy volunteers. Elevated serum sFas levels were also detected in patients with systemic lup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 18 publications
7
66
0
Order By: Relevance
“…than in healthy donors (HDs), although the level of serum soluble Fas ligand did not differ between SPs and HDs (Tomokuni et al, 1997(Tomokuni et al, , 1999. The mean fluorescent intensity (MFI) of membrane 4.…”
Section: Silica Particles and Dysregulation Of Immune Response Leadinmentioning
confidence: 93%
“…than in healthy donors (HDs), although the level of serum soluble Fas ligand did not differ between SPs and HDs (Tomokuni et al, 1997(Tomokuni et al, , 1999. The mean fluorescent intensity (MFI) of membrane 4.…”
Section: Silica Particles and Dysregulation Of Immune Response Leadinmentioning
confidence: 93%
“…In addition, our previous results indicated that in silicosis patients, who did not manifest clinical signs and symptoms of autoimmune diseases, possessed the dysregulation of Fas-mediated apoptotic pathway in their lymphocytes and was disrupted (5)(6)(7)(8)(9)(10)(11). Therefore, autoimmunity may be affected at the cellular level in these patients.…”
mentioning
confidence: 99%
“…Anti-Fas autoantibody detected in SILs was functionally active and caused Fas-mediated apoptosis (takata- . The level of serum sFas was higher in SILs than healthy volunteers (HVs), although the level of serum soluble FasL did not differ between SILs and HVs (Tomokuni, 1997. The mean fluorescent intensity (MFI) of membrane Fas was lower with lymphocytes from SILs than those from HVs, although total numbers of Fas-positive lymphocytes (membrane Fas expression) did not differ between the two populations .…”
Section: Alteration Of Fas/cd95 and Its Related Molecules In Silsmentioning
confidence: 90%